Magnesium Alloys - Properties in Solid and Liquid States 2014
DOI: 10.5772/59181
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Materials in Liquid Magnesium Alloys and Its Prevention

Abstract: According to early research [14], the corrosive attacks are classified as: (i) simple dissolution, (ii) alloying between liquid metal and solid metal, (iii) intergranular penetration, (iv) impurity reactions, (v) temperature gradient mass transfer, (vi) concentration-gradient mass transfer or dissimilar-metal mass transfer. As variables controlling liquid metal corrosion, such factors as temperature, its gradient or cyclic fluctuation, surface area to volume ratio, metal purity, flow velocity and some characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Over the past two decades, various surface modification strategies have been investigated to overcome the limitations of Mg and its alloys for biomedical applications . Interfacial engineering is one of the promising approaches, which could improve mechanical integrity, enhance corrosion resistance, control biodegradation, and promote the biocompatibility of Mg and its alloys .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, various surface modification strategies have been investigated to overcome the limitations of Mg and its alloys for biomedical applications . Interfacial engineering is one of the promising approaches, which could improve mechanical integrity, enhance corrosion resistance, control biodegradation, and promote the biocompatibility of Mg and its alloys .…”
Section: Introductionmentioning
confidence: 99%
“…Mg x Ni y intermetallic compounds or alloys are also expected to form at the inner tube surface. However, it was reported that these compounds could not inhibit diffusion of nickel [7]. Consequently, selective dissolution of nickel is likely to occur continuously.…”
Section: Failure Mechanismmentioning
confidence: 98%
“…Outward migration of nickel is known to cause nickel depletion in the base material, which impairs resistance to high temperature corrosion of nickel-based alloy [18]. Selective leaching of nickel due to its relatively high solubility in liquid metals, leading to selective corrosion, was also reported to change the alloys composition, resulting in component failure [1,7]. Magnesium is also detected in the scale established at the inner wall of the cold zone in the form of elemental magnesium.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Mg alloys are commonly melted and held in carbon steel, stainless steel or cast iron crucibles owing to the low solubility of Fe in liquid Mg. However, alloying elements such as Al in AMand AZ-series Mg alloys can react with the steel resulting in a Al-Fe(-Mn) reaction layer [1][2][3][4][5]. A small but important amount of Fe, meanwhile, can be picked up through the reaction layer into the melt to create Al-Mn(-Fe) IMC particles that can settle down to the bottom of crucibles and create sludge [6][7][8] and have a negative impact on corrosion performance if they enter the final casting.…”
Section: Introductionmentioning
confidence: 99%